2000
DOI: 10.1128/iai.68.9.5044-5049.2000
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Protease from a Mixture of Exfoliative Toxin and Newborn-Mouse Epidermis

Abstract: Although the role of exfoliative toxin in staphylococcal scalded-skin syndrome has been suggested to be that of a serine protease, it has not been demonstrated to show proteolytic activity. Our purpose was to purify a proteolytic enzyme from a mixture of exfoliative toxin and newborn-mouse epidermis. We used gel filtration and ion-exchange and hydroxyapatite chromatography with a high-pressure liquid chromatography system. A casein-hydrolyzing enzyme was isolated from the mixture. The molecular mass of the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The closely related cadherins such as desmoglein 3 were not affected. These data contradicts the suggestions by Ninomiya et al (2000), that the interaction of ET with epidermal component(s) induces proteolytically active enzyme. In addition, both toxins were shown to cleave α-melanocyte-stimulating hormone but only ETA cleaved β-melanocyte-stimulating hormone.…”
Section: Epidermolytic Toxinscontrasting
confidence: 99%
See 2 more Smart Citations
“…The closely related cadherins such as desmoglein 3 were not affected. These data contradicts the suggestions by Ninomiya et al (2000), that the interaction of ET with epidermal component(s) induces proteolytically active enzyme. In addition, both toxins were shown to cleave α-melanocyte-stimulating hormone but only ETA cleaved β-melanocyte-stimulating hormone.…”
Section: Epidermolytic Toxinscontrasting
confidence: 99%
“…The epidermolytic toxins have an intrinsic esterase activity, while ETA S195G active site serine mutant is inactive (Bailey and Redpath, 1992) and completely devoid of biological activity (Prévost et al, 1991;Redpath et al, 1991). On the other hand, Ninomiya et al (2000) reported the isolation of a protease corssreacting with anti-ET antibodies and readily hydrolyzing casein, but with molecular weight lower than the toxins, from the mixture of exfoliative toxin and newborn-mouse epidermis. Neither could the epidermal splitting in the mouse bioassay be completely inhibited by DFP, although the treatment prolonged the time needed for epidermolysis to occur (Dancer et al, 1990).…”
Section: Epidermolytic Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies ETA has been shown to cleave ␣-and ␤-melanocyte stimulating hormones after a lengthy incubation period ; however, it is unclear how this might result in or contribute to SSSS or BI. Also, other investigators studying ETB have purified a distinct 20 kDa protease from a supernatant of preparations of neonatal mouse epidermis treated with ETB which was able to reproduce epidermolysis similar to that of SSSS when injected into neonatal mice (Ninomiya et al, 2000). These results would suggest the presence of an additional target for the ETB versus ETA, as Dsg1 has been shown to be cleaved by both ETB and ETA (Amagai et al, 2000;Amagai et al, 2002).…”
Section: Clincal Conditions Caused By the Exfoliative Toxin Producingmentioning
confidence: 82%
“…The authors suggest that these proteins may be the target for the toxins. On the other hand, a Japanese group isolated and purified a distinct 20 kDa protease from a supernatant of exfoliative toxin with neonatal mouse epidermis and showed that this protease could reproduce the mid‐epidermal splitting of SSSS when injected subcutaneously into newborn mice [43].…”
Section: Pathogenesismentioning
confidence: 99%